2008
DOI: 10.1677/jme-08-0146
|View full text |Cite
|
Sign up to set email alerts
|

Cell cycle control of pituitary development and disease

Abstract: The pituitary gland regulates diverse physiological functions, including growth, metabolism, reproduction, stress response, and ageing. Early genetic models in the mouse taught us that the pituitary is highly sensitive to genetic alteration of specific cell cycle regulators such as the retinoblastoma protein (pRB) or the cell cycle inhibitor p27 Kip1 . The molecular analysis of human pituitary neoplasias has now corroborated that cell cycle deregulation is significantly implicated in pituitary tumorigenesis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
68
0
7

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(81 citation statements)
references
References 106 publications
6
68
0
7
Order By: Relevance
“…Interestingly, crossing of p18-null mice with mice deficient for other Cdk inhibitors, such as p16, p27, or p21, led to double mutant mice with increased incidence and decreased latency in the development of pituitary adenomas as compared with single mutant mice (Franklin et al 1998, Ramsey et al 2007. Therefore, the existence of two major pathways for G 1 /S phase dysregulation in pituitary tumors has been suggested: one involving p18/CDK4/pRB, and the other one involving p27 and p21 (Quereda & Malumbres 2009). Consistently, knock-in mice, which express a Cdk4 mutant originally found in human melanoma (Wölfel et al 1995) and which are insensitive to INK4 inhibitors (Cdk4 R24C), develop several tumors, including pituitary adenomas (Sotillo et al 2001, Rane et al 2002.…”
Section: The Cell Cyclementioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, crossing of p18-null mice with mice deficient for other Cdk inhibitors, such as p16, p27, or p21, led to double mutant mice with increased incidence and decreased latency in the development of pituitary adenomas as compared with single mutant mice (Franklin et al 1998, Ramsey et al 2007. Therefore, the existence of two major pathways for G 1 /S phase dysregulation in pituitary tumors has been suggested: one involving p18/CDK4/pRB, and the other one involving p27 and p21 (Quereda & Malumbres 2009). Consistently, knock-in mice, which express a Cdk4 mutant originally found in human melanoma (Wölfel et al 1995) and which are insensitive to INK4 inhibitors (Cdk4 R24C), develop several tumors, including pituitary adenomas (Sotillo et al 2001, Rane et al 2002.…”
Section: The Cell Cyclementioning
confidence: 99%
“…Crossing of Cdk4 R24C/R24C mice with mice deficient for p27 (but not with those deficient for p18) generates mice that develop pituitary adenomas with higher incidence and shorter latency than compound Cdk4 knock-in mice (Sotillo et al 2005). Moreover, a dramatic cooperation in pituitary tumor development has been observed in mutant mice carrying a combination of the Cdk4 R24C, p21-null, and p27-null alleles (Quereda & Malumbres 2009). …”
Section: The Cell Cyclementioning
confidence: 99%
“…Recently, the model of "oncogene-induced senescence" (OIS) has been used to explain proliferative arrest promoting cellular senescence and thus playing a protective role in the non-progression to malignancy. 7,8 It has been shown that senescence is mediated by oncogenic activity which triggers the activation of different cell-cycle regulators such as p53 and pRb to mediate the senescence pathways: 9 the influence of a particular oncogene on its downstream effectors increases progressively during tumour development, with senescence being triggered at a point when tumours have already been initiated but have not reached a fully malignant phenotype. 10 It has been suggested that OIS requires time to develop, following an initial proliferative phase but eventually resulting in a benign tumour with stable growth arrest, as is the case of pituitary adenoma growth.…”
Section: Introductionmentioning
confidence: 99%
“…These pituitary tumors were usually accompanied with hyperplasia of other endocrine tissues, such as the Langerhans islets in the pancreas or adrenal gland, as well as hyperplasia of Leydig cells in the testis (Supplementary Table S1 and Supplementary Figure S1). The aberrations in the pituitary gland, frequently altered in mouse models of cell-cycle deregulation, 24 are summarized in Table 1 and Supplementary Table S2. Lack of p27 Kip1 , or the combined loss of p21 Cip1 and p27 Kip1 , resulted in pars intermedia tumors whereas the activating R24C mutation in Cdk4 generated tumors in the pars distalis (Supplementary Table S2; Sotillo et al 19 ).…”
Section: Resultsmentioning
confidence: 99%